IL-23 Induces Atopic Dermatitis-Like Inflammation Instead of Psoriasis-Like Inflammation in CCR2-Deficient Mice - Bromley, Shannon K.; Larson, Ryan P.; Ziegler, Steven F.; Luster, Andrew D. (PLOS ONE, 2013)
Psoriasis is an immune-mediated chronic inflammatory skin disease, characterized by epidermal hyperplasia and infiltration of leukocytes into the dermis and epidermis. IL-23 is expressed in psoriatic skin, and IL-23 injected into the skin of mice produces IL-22-dependent dermal inflammation and acanthosis. The chemokine receptor CCR2 has been implicated in the pathogenesis of several inflammatory diseases, including psoriasis. CCR2-positive cells and the CCR2 ligand, CCL2 are abundant in psoriatic lesions. To examine the requirement of CCR2 in the development of IL-23-induced cutaneous inflammation, we injected the ears of wild-type (WT) and CCR2-deficient (CCR2−/−) mice with IL-23. CCR2−/− mice had increased ear swelling and epidermal thickening, which was correlated with increased cutaneous IL-4 levels and increased numbers of eosinophils within the skin. In addition, TSLP, a cytokine known to promote and amplify T helper cell type 2 (Th2) immune responses, was also increased within the inflamed skin of CCR2−/− mice. Our data suggest that increased levels of TSLP in CCR2−/− mice may contribute to the propensity of these mice to develop increased Th2-type immune responses.